Distance on Timed Words and Applications - Asarin, Eugene; Basset, Nicolas; Degorre, Aldric (Formal Modeling and Analysis of Timed Systems, 2018)
We introduce and study a new (pseudo) metric on timed words having several advantages:it is global: it applies to words having different number of events;it is realistic and takes into account imprecise observation of timed events; thus it reflects the fact that the order of events cannot be observed whenever they are very close to each other;it is suitable for quantitative verification of timed systems: we formulate and solve quantitative model-checking and quantitative monitoring in terms of the new distance, with reasonable complexity;it is suitable for information-theoretical analysis of timed systems: due to its pre-compactness the quantity of information in bits per time unit can be correctly defined and computed.